Crio laser forese utilizado como um método biofísico na promoção da penetração cutânea da cafeína - Lopes, Fabia Leal [UNIFESP] (2017)
The main barrier to topical treatment systems is related to the ability of the active substance to pass through the stratum corneum. Thus, studies on penetration promoters have intensified. The objective of this work was to evaluate the efficacy of the biophysical method called Cryo Laser Forese (CLF) in the cutaneous penetration of caffeine, using Franz cell with vertical diffusion. Formulas with and without caffeine were prepared and frozen at -18 °C, followed by a preliminary study of spectrophotometer stability in the visible ultraviolet (UV-Vis) region. The Cryo Laser Forese was applied or not to the human skin with the formulations during 10 minutes. After 24 hours of application of the Crio Laser Forese, the cells were disassembled and separated into epidermis and dermis. Receptor, epidermal and dermal fluid samples were analyzed by HPLC with a diode arrangement detector (HPLC-UV/ DAD). The results of the permeation test suggest that CLF did not contribute to the permeation of caffeine under the conditions studied. The same experiment was performed for histological study of the skin and after 24 hours of application of the Cryo Laser Forese, the skins were fixed, stained and the prepared sheets. Photomicrographs of the slides were performed under an optical microscope at 40X magnification. Histological sections showed no alterations, as did the cell viability assessment test, suggesting that the equipment studied does not cause damage to the skin. Before the permeation tests, two models of biological membranes were compared: in vitro and ex vivo. In the in vitro test, the dermoepidermal equivalents were assembled using fibroblasts and human keratinocytes. For the ex vivo membrane, abdominal human skin was taken from plastic surgeries. When we compared the membranes, the dermoepidermal model in vitro was more permeable than ex vivo human skin.